(untitled) (International Journal of Nursing Education, 2019)
Background: Pregnancy is unique, exciting, often joyous time in women life as she gives birth to baby. It is the time, when she receives extra care and support from husband and family. It is a vital aspect of women’s life and even Government is also undertaking various programmes and schemes which safeguard the life of both mother and baby during Pregnancy. Although pregnancy is a special period but Puerperium is a period which cannot be neglected as two lives comes which is vulnerable section of society1. This period is not only the termination of pregnan Puerperium is a time of great importance for both the mother and the baby; but has received relatively less attention compared with antenatal (pregnancy) and intranatal (delivery) period. Aims: The study aims to assess the knowledge and practice regarding prevention of puerperal infection among postnatal mothers by prepared an information booklet regarding prevention of puerperal infection. Methodology: The research approach for this study was quantitative approach, the research design For the present study, non experimental descriptive research design. The sample size of the present study was 120 postnatal mothers selected by purposive sampling technique. Conclusion: Near about more than half of the postnatal mothers had average knowledge 63.33% regarding prevention of puerperal infection and 52.5% had unsatisfactory practices regarding prevention of puerperal infection.